Are there racial/ethnic differences in antibiotic treatment of community acquired pneumonia in the inpatient setting? - Shana A. B. Burrowes; Mari-Lynn Drainoni; Tamar F. Barlam (PLoS ONE, 2026)
Background Community Acquired Pneumonia (CAP) is the most common reason for antibiotic treatment in hospitalized adults. Some prior studies have found treatment differences by race/ethnicity, but research on the topic is limited, results are mixed, and it is unclear if clinical outcomes are affected. Methods We conducted a retrospective analysis of hospitalized patients >=18 years of age with a diagnosis of CAP from 2018–2021 across 457 US hospitals in the Vizient Inc. Clinical Data Base. We examined guideline concordant antibiotic treatment differences for inpatient CAP by patient race/ethnicity and hospital level factors and secondarily assessed whether treatment differences affect patient clinical outcomes. Results There were 1,277,770 admissions. Over half of all patients received concordant antibiotic therapy. Non-Hispanic Black patients had an increased odds of receiving guideline concordant antibiotic care (OR 1.22 95% CI 1.21–1.23) compared to non-Hispanic White patients. As the number of hospital beds increased, the odds of receiving concordant therapy decreased, with the greatest reduced odds between hospitals with >500 beds vs < 75 beds (OR 0.68, 95% CI 0.66–0.70). As case mix index increased concordant care decreased with the lowest odds observed at hospitals with a case mix index >2 (OR 0.71 95% CI 0.7–0.72). Patients at hospitals in the South (OR 0.8 95% CI 0.79–0.81) and Northeast (OR 0.71, 95% CI 0.7–0.72) were less likely than those in the West to receive concordant care. There was no significant association between the interaction of race/ethnicity and receipt of guideline concordant therapy and clinical outcomes. Conclusion Non-Hispanic Black patients were more likely to received guideline-concordant care for CAP however significant differences in concordant therapy were seen at the hospital level. Understanding the interplay of race/ethnicity and concordant CAP therapy at the individual and population level is important for future research in the examination of disparities in care.